Effect of ozone and vapor phase hydrogen peroxide fumigation on the control of postharvest diseases of longan fruit (Dimocarpus longan lour.) - Whangchai K. (2014)
This study evaluated the effect of vapour phase hydrogen peroxide (VPHP) at different fumigation times and temperatures. The combination of VPHP and 200 ppm ozone for 60 minutes to control the decay of fresh longan fruit during storage was also investigated. The results showed that fumigation with VPHP for 60 minutes at 60°C was the most effective condition to reduce disease incidence in longan fruit during storage at 5°C for 21 days. Exposure of longan fruit to VPHP combined with ozone or VPHP alone significantly reduced microbial population compared to control. However, the combination of ozone and VPHP treatment had better results in controlling browning and reduction of polyphenol oxidase (PPO) activity.